Use the path analysis method to diagnoseFactors influencing the intentions of the employees of the University of Dhi Qar To introduce Internet behavior - دريفش عبد العظيم (Journal of Economics and Administrative Sciences, 2009)
The purpose of this study is to diagnose factors that effect Thi-Qar behavioral intention to use internet. A sample of (127) internet users of university staff was taken in the study and were analyzed by using path analyze . The study concluded that there is a set of affecting correlation. It was founded that exogenous variables (gender, income, perceived fun, perceived usefulness, Image, and ease of use) has significant effect on endogenous (behavioral intention) . The result of analysis indicated that image hopeful gained users comes first, ease of use secondly, perceived fan and perceived usefulness on (dependent variables (daily internet usage and diversity of internet usage. Implication of these result are discussed . the study ended with recommendation stress the importance of such factors and the need of exploiting them to enhance internet use.